Navigating do not resuscitate orders: the involvement of critical care nurses in Malaysia - Mohamad Sohaimi, Hafizah; Wan Mamat, Wan Hasliza; Mohd Ali, Noor Azizah; Atan, Ashikin (Universiti Putra Malaysia, 2025)
Introduction: As primary caregivers, critical care nurses play a crucial role in the implementation of do not resuscitate (DNR) orders, ensuring that a patient’s rights is respected while providing compassionate and effective care. However, there remains a gap in understanding the experiences and involvement of nurses in DNR orders, particularly in Malaysia. Objective: This study aims to explore the involvement of critical care nurses in DNR orders. Method: This study employed a qualitative research design and purposive sampling was used to recruit 12 nurses from an intensive care unit in one of the teaching hospitals in Malaysia. Semi-structured interviews were conducted to explore the participants’ experiences in caring for patients issued with DNR orders. The data was analysed using thematic analysis. Result: Three main themes emerged from the data: 1) providing spiritual care; 2) limited roles in DNR orders decision; and 3) power imbalance. Conclusion: This study highlights the significant role played by critical care nurses in the implementation of DNR orders. Support from healthcare institutions is needed to enhance the nurses’ roles and skills while fostering a collaborative environment where nurses can effectively participate in DNR decision-making process.